Volume 3 - Berstrom, Lars; Berstrom, Lars (Singapore, 2001)
Includes bibliographical references.; v. 1. Lectures by C.N. Yang and S. Weinberg with translated reprints by O. Klein / editor, GoÌˆsta Ekspong -- v. 2. Lectures by Hans A. Bethe and Alan H. Guth with translated reprints by Oskar Klein / editor, GoÌˆsta Ekspong -- v. 3. [without special title] / editors, Lars BergstroÌˆm & Ulf LindstroÌˆm
Keywords: Klein, Oskar.; Physics.; Quantum theory.; Physicists -- Sweden -- Biography.; Vật lý; Lý thuyết lượng tử; Nhà vật lý học -- Tiểu sử -- Thụy Điển